Trajectory tracking control method based on adaptive super-twisting sliding mode - QI Zhaohui; ZHANG Jin; WANG Yuanzhuo; WANG Jia; XU Mengrong; ZHANG Cheng (Xibei Gongye Daxue Xuebao, 2022)
Aiming at the problem of trajectory tracking control in the process of missile network formation flying, based on the optimal nominal trajectory obtained by solving the two-point boundary value problem, combined with the anti-jamming characteristics of the sliding mode controller, a trajectory tracking control method based on the adaptive super-twisting sliding mode is proposed. First, on the basis of the terminal guidance section model, the two-point boundary value problem is solved through the idea of nonlinear programming to obtain the optimal nominal trajectory; Secondly, the tracking controller based on state deviation is designed in combination with the adaptive super-twisting sliding mode algorithm; Finally, the LQR trajectory tracking control method is introduced as a comparison method, and the effectiveness and feasibility of the sliding mode trajectory tracking method in the presence of initial state errors are verified by simulations, and the Monte Carlo simulation shows that the proposed method has good trajectory tracking control effect in the presence of different initial state errors.